Humanitarian slaughter and desensitization in cattle from the perspective of legal veterinary medicine: Review - Amaral, Jackson Barros do; Tremori, Tália Missen; Santos d’Alencar, Alessandra; Trevisan, Guilherme (Pubvet, 2019)
This review has the objective to discuss the main critical points of the humanitarian slaughter of bovines with approaches necessary for audits and fundaments for expert report. The Brazilian beef production has great importance in agribusiness, with national and international prominence. Currently, the population's concern about the welfare of production animals has been growing, making investments in scientific research and humanitarian education in all segments of the production chains. In the past decades the slaughter of production animals had been considered a technological procedure of inferior scientific grade, not composing a subject studied by universities, research institutes and industry. Subsequently, this issue gained importance when it was evident the influence of the quality of meat and its products in national and international trade. Following the obvious influences of the World Organization for Animal Health (OIE) and the International Humanitarian Society (HSI), the demand for source products of animals raised, handled, transported and slaughtered through the use of humanitarian practices grew up. It should be considered that animal welfare does not necessarily correspond to sanitary quality, but rather an ethical and moral concern of consumers. The Ministry of Agriculture, Livestock and Food Supply in Brazil (MAPA) predicts that until 2020 the Brazilian meat production will provide 44.5% of the world market, this being the great challenge of Brazil to maintain effective measures of humanitarian slaughter and to lead as a world exporter of bovine meat To slaughter animals under humanitarian conditions is a moral duty of man, and each country must establish strict regulations in order to guarantee this condition to all species. Conventional methods of slaughter of cattle involve the pre-desensitization of bleeding, except slaughtering conducted according to Jewish or Islamic rituals. The actions of audits and legal veterinary medicine have an important contribution in the settlement of judicial and etical issues in this process. So is necessary to invest in studies and discussions on the improvement of this important topic for use in audits and in the definition of an expert protocol aimed at humanized slaughter.
Keywords: animal welfare; cattle breeding; expertise; slaughterhouse; veterinary forensic medicine